Comprehensive analysis based on the ubiquitination- and deubiquitylation-related genes reveals the function of NEURL3 in esophageal squamous cell carcinoma - Lin, Yi-Wei; Li, Hui-Er; Hong, Chao-Qun; Chen, Zi-Ang; Liu, Shu-Ping; Xu, Yi-Wei; Wu, Fang-Cai; Peng, Yu-Hui (Frontiers in Immunology, 2025)
BackgroundAs a highly invasive gastrointestinal malignancy, esophageal squamous cell carcinoma (ESCC) carries with its high morbidity and mortality. Accumulating evidence indicates that abnormal activation of ubiquitination and deubiquitylation has been implicated in pathophysiology of ESCC. However, rare prognostic models for ubiquitination-related genes (URGs) and deubiquitylation-related genes (DRGs) have been built up in ESCC.MethodsFrom training dataset GSE53624, the differentially expressed prognostic URGs and DRGs were identified to develop a prognostic signature, which was validated in GSE53622 and TCGA-ESCC dataset to show the robustness of the signature. To further confirm their prognosis value, the unsupervised clustering analysis was used to develop the molecular subtypes based on the prognostic URGs and DRGs. Differences in terms of biological function, immune status, and drug sensitivity were evaluated between high- and low-risk groups. The nomogram was constructed by combining the URGs and DRGs prognostic signature and clinical characteristics to improve prediction efficacy. Loss-of-function studies were conducted to explore the biological function of NEURL3 in ESCC.ResultsThe URGs and DRGs prognostic signature consisted of 11 genes and exhibited high accuracy in predicting prognosis of ESCC patient. Based on these 11 URGs and DRGs, two molecular subtypes of ESCC (C1 and C2) were identified, of which C2 subtype had significantly shorter overall survival time than that of C1 subtype. The function enrichment analysis showed that these genes play key roles in essential processes such as tumor metastasis and immune response. Moreover, the risk score was closely related to infiltration abundance of some types of immune cells, gene markers of immune cells and immune checkpoint-related markers. The drug sensitivity analysis showed that dacomitinib and talazoparib may serve as anti-ESCC drugs through targeting MAPK14. The nomogram was established by combining the URGs and DRGs signature with age and TNM stage, and it also showed enhanced prognostic predictive accuracy. The in vitro experiments showed that knockdown of NEURL3 inhibited the proliferation and motility of ESCC cells.ConclusionsBased on the URGs and DRGs prognostic signature, a novel nomogram was constructed that could serve as a potentially reliable prognostic model and provide theoretical basis for uncovering potential therapeutic target in the treatment of ESCC.